Repurposing Candesartan Cilexetil as Antibacterial Agent for MRSA Infection - Xu, Lanlan; She, Pengfei; Chen, Lihua; Li, Shijia; Zhou, Linying; Hussain, Zubair; Liu, Yaqian; Wu, Yong (Frontiers in Microbiology, 2021)
Abstract: Staphylococcus aureus is an important pathogen causing hospital-acquired infections. Methicillin-resistant S. aureus (MRSA), biofilms and persisters highly tolerant to traditional antibiotics make it difficult to treat. Therefore, new antimicrobial agents are urgently needed to treat hard-to-eradicate diseases caused by this bacterium. In this study, candesartan silexites (CC), an antigenic hypertension drug, had strong antimicrobial activity against S. aureus with minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs) of 8-16 μg/mL and 16-32 μg/mL. CC exhibited limited cytotoxicity and low possibility to induce drug resistance. In addition, it showed a synergistic antibacterial effect when combined with gentamicin and tobramycin. The effective concentrations to inhibited MRSA biofilm formation were 16-64 μg/mL and it killed intractable persisters at 4-8 × MIC. Through the analysis of its mechanism of action, it was evident that the membrane permeability was disrupted as well as the cell structure was damaged. Furthermore, we demonstrated that CC had antibacterial effects in vivo through MRSA-infected murine skin abscess models. In conclusion, these results implied that CC might be a potential antibacterial agent for the treatment of S. aureus-associated infections.